Effects of sorghum particle size on milling characteristics, growth performance, and carcass characteristics in finishing pigs - C B Paulk; Joe D Hancock; Adam C Fahrenholz; J M Wilson; Leland J McKinney; Keith C Benhke (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 200 finishing pigs (PIC TR4 × 1050; average initial BW of 103.2 lb) were used in a 69-d growth assay to determine the effects of sorghum particle size on growth performance. Pigs were sorted by sex and ancestry and balanced by BW, with 5 pigs per pen and 10 pens per treatment. Treatments were a corn-soybean meal-based control with the corn milled to a target mean particle size of 600 Î¼m, and sorghum diets milled to a target mean particle size of 800, 600, or 400 Î¼m. Actual mean particle sizes were 555 Î¼m for corn, and 724, 573, and 319 Î¼m for sorghum, respectively. Feed and water were offered on an ad libitum basis until the pigs were slaughtered (average final BW of 271 lb) at a commercial abattoir. Reducing sorghum particle size improved (linear, P<0.01) F/G, and we observed a tendency for decreased (P<0.06) ADFI. Reducing sorghum particle size from 724 to 319 Î¼m had no effects on HCW, backfat thickness, loin depth, or percentage fat-free lean index (FFLI), but tended to increase (P<0.06) carcass yield. Pigs fed the sorghum-based diets had no difference in growth performance or carcass characteristics compared with those fed the control diet, except carcass yield, which was numerically greater (P<0.07) for pigs fed the sorghum-based diets. When using a regression equation, we determined that sorghum must be ground to 513 Î¼m to achieve a F/G equal to that of a corn-based diet, with corn ground to 550 Î¼m. In conclusion, linear improvements in F/G and carcass yield were demonstrated with the reduction of sorghum particle size to 319 Î¼m. In this experiment, sorghum should be ground 42 Î¼m finer than corn to achieve a similar feeding value.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Corn; Particle size; Sorghum; Finishing pig